Practice-based community service through P3NKK internship at Telkom University Open Library - Nasya Putri Fadilla (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Program Penguatan Profesional Kepustakaan Non Kependidikan (P3KNK) is a practice-based community service initiative that enhances students’ professional competencies through direct experience in an academic library. The program was conducted at Telkom University Open Library over 40 working days (November 18, 2024–January 24, 2025) and involved three students from the Library and Information Science study program. The program employed a structured rotation system across three service areas: circulation services (17 days), reference services (13 days), and library material processing (10 days). The methods included hands-on practice, participatory observation, guided discussions, and continuous mentoring by professional librarians. The results demonstrate that the students made tangible contributions to library operations, including processing 204 scholarly documents for e-proceedings, handling 51 library clearance letters, cataloging 83 e-books, and processing 61 donated collections. The program also significantly enhanced students’ technical skills (cataloging, classification, and library technologies) as well as soft skills (communication, problem-solving, and professionalism). In addition, six key operational challenges were identified, along with proposed solutions to improve service. Overall, the P3KNK program effectively bridges academic theory and professional librarianship practice.   Abstrak Program Penguatan Profesional Kepustakaan Non Kependidikan (P3KNK) merupakan kegiatan pengabdian berbasis praktik yang bertujuan memperkuat kompetensi profesional mahasiswa kepustakawanan melalui pengalaman kerja langsung di perpustakaan perguruan tinggi. Program ini dilaksanakan di Telkom University Open Library selama 40 hari kerja (18 November 2024–24 Januari 2025) dengan melibatkan tiga mahasiswa Program Studi Perpustakaan dan Sains Informasi. Pelaksanaan program menggunakan sistem rotasi terstruktur pada tiga area layanan, yaitu layanan sirkulasi (17 hari), layanan referensi (13 hari), dan pengolahan bahan pustaka (10 hari), dengan metode praktik langsung, observasi partisipatif, diskusi terpandu, dan pendampingan pustakawan. Hasil pengabdian menunjukkan kontribusi nyata mahasiswa terhadap operasional perpustakaan, antara lain pengolahan 204 dokumen e-prosiding, pelayanan 51 Surat Bebas Kewajiban Perpustakaan, katalogisasi 83 e-book, dan pengolahan 61 koleksi sumbangan. Program ini juga meningkatkan kompetensi teknis (katalogisasi, klasifikasi, dan pemanfaatan teknologi perpustakaan) serta kompetensi non-teknis (komunikasi, pemecahan masalah, dan profesionalisme). Selain itu, teridentifikasi enam permasalahan operasional utama beserta alternatif solusi sebagai bahan perbaikan layanan. Secara keseluruhan, P3KNK efektif menjembatani teori akademik dan praktik profesional kepustakawanan. Kata Kunci: P3KNK; pengabdian berbasis praktik; perpustakaan perguruan tinggi; praktik profesional